IgG4-related uveitis. A French cohort and literature review - Stuchfield-Denby, Emily; De Sainte Marie, Benjamin; Hie, Miguel; Hatchuel, Yves; Gerber, Anne; Bencheikh, Saliha; Pugnet, Grégory; Groh, Matthieu; Farhat, Meryem-Maud; Urbina, Diego; Ebbo, Mikael; Schleinitz, Nicolas (Seminars in arthritis and rheumatism, 2024)
IgG4-related disease (IgG4-RD) is a fibro-inflammatory disorder that can affect almost any organ. IgG4-related ophthalmic disease is a protean condition involving the orbit and ocular adnexa. Although a few cases of uveitis have been reported, the exact pattern of IgG4-related intraocular manifestations remains unclear. Here, we report on a nationwide French multicenter cohort of patients with IgG4-RD and uveitis and conducted a literature review. Patients with uveitis and a concomitant definite diagnosis of IgG4-RD (Revised Comprehensive Diagnostic criteria, American College of Rheumatology/European League Against Rheumatism classification criteria for IgG4-RD, International Consensus Diagnostic Criteria for auto-immune pancreatitis, or diagnostic criteria for IgG4-related hypophysitis), were screened from our national IgG4-RD and systemic fibrosis database. Concomitantly, we conducted a PubMed literature review and selected cases of definite IgG4-RD with uveitis. We reported on 16 patients (8 from our database and 8 from the literature) and a total of 30 episodes of uveitis. Uveitis cases represented 3 % of total IgG4-RD patients in the national database on IgG4-RD and systemic fibrosis. Uveitis was inaugural in IgG4-RD in 4/16 cases (25 %) (appearing before any other IgG4-related symptom, at a median of 9 months), occurred concurrently to other IgG4-related symptoms in 9/16 cases (56 %) (at a median of 15 months before IgG4-RD diagnosis), and appeared during follow up in 3/16 patients (19 %) (at a median of 57 months after first IgG4-related symptoms). When uveitis occurred during follow up, it was associated with IgG4-RD manifestations in other organs in 6/9 patients (67 %). Uveitis was bilateral in 8/16 cases (50 %) and granulomatous in 5/10 cases (50 %). It was anterior in 8/13 (62 %), intermediate in 3/13 (23 %), and global (panuveitis) in 4/13 patients (31 %). Median serum IgG4 at diagnosis was 3.2 g/L. Median follow up time was of 6 years, during which 8/16 patients (50 %) experienced at least one relapse of uveitis. Treatment data was available for 29/30 uveitis flares. Steroids were used in 28/29 episodes of uveitis (97 %), leading to remission of uveitis in 16/28 cases (57 %). Methotrexate and rituximab (in combination with systemic steroids) were administered as second- or third-line therapy in 6/29 (21 %) and 5/29 (17 %) episodes of uveitis, respectively, and led to remission of uveitis in 4/6 cases (67 %) and 4/5 cases (80 %), respectively. One third of uveitides required at least two different lines of treatment for remission induction (mainly a combination of both systemic steroids and methotrexate or rituximab). Uveitis may be one of the initial symptoms of IgG4-RD, and IgG4-RD should be considered in the diagnostic workup of uveitis. Its early onset in IgG4-RD may help with early diagnosis and treatment of the disease. Steroid monotherapy may be sufficient to treat IgG4-related uveitis, yet relapses were frequent (50 %) and ultimately a third of patients required at least two lines of treatment. Hence, steroid-sparing agents can be considered at early stages of the disease, particularly for patients with a high risk of relapse or steroid-related complications.